An integrated review program for the preparation for the United States medical license examination (USMLE) - Rogers, P.; Niyazmetova, L.; Abdiyeva, K. (Nazarbayev University, 2014)
The primary objective of the present educational research program is to improve upon existing commercially available USMLE review programs. With the clear shortage of both residency slots, the medical student's performance (score), on the USMLE assumes a new and critical importance. Furthermore, there is a global need for 4.3 million new doctors and nurses. This shortage is particularly evident in Central and Southeast Asia. Many of the needed new doctors will most probably be required to pass the USMLE.
Keywords: USMLE review programs; medical license; program; integration; project; educational